بررسی خصوصیات نانو مواد مبتنی بر اکساید فلزی و استفاده آن¬ در حس¬گرهای الکترونیکی و الکتروکیمیاوی - Ayazi, Haseebullah; Maheen, Nazifullah (Farah Research and Scientific Journal, 2024)
Electrical and electrochemical sensors are devices that are used in most industrial, medical, and home sectors as a danger informer or detector of toxic gases and chemical substances. In recent years, due to the advancement of technology and various industries, the construction of these devices has also made significant progress. Pure, mixed, and doped metal oxides have attracted great interest for the development of electrical and electrochemical sensors because they are cheaper, faster, easier to operate, and capable of on-line and portable decomposition. Interesting results on the monitoring of biochemical substances such as dopamine, epinephrine, serotonin and glucose have also been reported using electrochemical sensors based on glassy carbon modified with hybrid nanocomposite and screen-printed carbon electrodes. The fundamental sensing mechanisms and commercial limitations of metal oxide-based electrical and electrochemical sensors are discussed, providing research directions to bridge the gap between new sensor concepts and real-world analytical applications. This review is focused on highly sensitive chemical type sensors based on metal oxide and doped metal oxide semiconductors, which are used to detect toxic gases (H2, CO, NO2) and volatile organic compounds, for example, acetone, ethanol, in the monitoring of gas indicators in the breathing of patients with special diseases and to control environmental pollution.